Floristic Composition and Characteristics of Xuzhou, China. Issue 1 (November 2020) - Ju, Shuming; Bu, Peijiao; Zhang, Yuting; Zhao, Huaxiang; Chen, Jiayi; Li, Peigen; Yang, Chengfang; Nan, Nan
Abstract: Located in the southeastern part of the North China Plain, Xuzhou is the northernmost city in Jiangsu Province. According to the investigation, there are 733 species of 462 genera and 127 species of wild plants in Xuzhou. According to the type of distribution area of families and genera, the proportion of the pantropical distribution is 31.50%, which is the largest in the tropical northern margin of Xuzhou. The total tropical composition is 144 genera, accounting for 31.17%. The temperate distribution has a total of 236 genera, accounting for 51.08%. According to the geographical composition of the subordinates, the wild flora of Xuzhou is mainly composed of temperate elements, and the typical temperate components account for 51.08%. Therefore, the wild flora of Xuzhou should be temperate flora.